Special issue on crisis/disaster management
aThe special issue outlines the impact of disasters in Nepal and identifies measures that are deemed critical for an administrative capacity to be able to respond to the full spectrum of catalysm affecting the Nepalese Kingdom. The paper on flood disasters in Bangladesh also indicated a growing capacity for, as well as a recognition of, the need to adapt administratively towards critically non-routine situations. The paper from the People's Republic of China reveales broader policy issues associated with managing the impact of disasters. This, together with a later paper on the specific experience of the Chinese government with earthquake disaster management gives information, especially with regard to the i
Keywords: Philippines; Nepal; Management; Flood; Earthquake; Disaster; China; Bangladesh; Australia; Alaska; Disaster Preparedness